Urgensi Penerapan Soal HOTS dalam Ujian dan Evaluasi Pendidikan Islam - Yusuf, M.; Aris Eko Cahyono (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This article discusses the significance of implementing Higher Order Thinking Skills (HOTS) questions in the context of Islamic education examinations and evaluations. In the face of the demands of the modern era, Islamic education must produce individuals who not only possess religious knowledge but are also capable of critical, analytical, and creative thinking in addressing various complex issues relevant to Islamic teachings. The aim of this article is to highlight the benefits derived from the application of HOTS questions within the context of Islamic education. Through a literature review and theoretical analysis, this article delves into the theoretical foundations of Higher Order Thinking Skills and their relevance within Islamic education. The methodology employed encompasses a descriptive-qualitative research approach with content analysis. The results indicate that the implementation of HOTS questions in Islamic education can enhance students' understanding of religious principles, prepare them to confront the complexities of the modern world, and cultivate critical thinking in alignment with Islamic values. Additionally, the article identifies several challenges that may arise in implementing HOTS questions in Islamic education, such as curriculum expansion and cultural adaptation